Predicting Marital Quality Based on Emotion Regulation, Self-Esteem, and Early Maladaptive Schemas in Women with Cervical Intraepithelial Neoplasia - Ghelichkhani, Maryam; Shahbeik, Soroush (Psychology of Woman Journal, 2024)
Objective: This study aimed to predict marital quality based on emotion regulation, self-esteem, and early maladaptive schemas in women with cervical intraepithelial neoplasia. Methods and Materials: The research method was descriptive and correlational. The statistical population of the present study included all married women with cervical intraepithelial neoplasia who referred to specialized gynecologic oncology surgery centers in Tehran in 2022. A total of 120 individuals were selected through purposive sampling and responded to research instruments, including the Marital Quality Questionnaire (Busby et al., 1995), the Emotion Regulation Questionnaire (Gross & John, 2003), the Self-Esteem Questionnaire (Coopersmith, 1967), and the Early Maladaptive Schemas Questionnaire (Young, 2005). Data were analyzed using Pearson correlation coefficient and multiple regression analysis with SPSS software version 26. Findings: The findings indicated that there is a significant inverse correlation between the overall score of early maladaptive schemas and each of its dimensions and the emotional inhibition dimension of emotion regulation with marital quality in the sample individuals (P<0.05). This relationship between the cognitive reappraisal dimension of emotion regulation and self-esteem with marital quality was positive and significant. Additionally, simultaneous entry regression analysis showed that the predictor variables together could explain 32% of the variance in the marital quality score. Conclusion: In general, it can be concluded that psychological variables, including early maladaptive schemas, emotion regulation, and self-esteem, can predict marital quality in women with cervical intraepithelial neoplasia. Therefore, the importance of these psychological variables should not be overlooked in improving the marital quality of this group of women.